(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article presents information about the negative impact on the socio-economic life of society and the severe tragic consequences as a result of illegal actions carried out during the period of repression against the “Cotton affair” in Uzbekistan, in particular, in the Navoi region. The investigation team led by Gdlyan uses illegal methods in the investigation process and makes false accusations against the accused. The article analyzes the violation of the rights and freedoms of the accused, who were unjustly punished as criminals and caused suffering, using the example of victims of repression.